Case Report: Management of intracranial hypertension in acute-on-chronic liver failure: a case of fulminant cerebral edema and acute-onset severe hyperammonemia in a patient with cirrhosis - Tang, Wei; Dawkins, Makeda; Kumar, Anila; Nasereldin, Mohammed; Heering, Gabriel; Soffler, Morgan; Wolf, David C. (Frontiers in Gastroenterology, 2025)
Intracranial hypertension (ICH) is a well-recognized and potentially fatal complication of acute liver failure. It is rarely observed in patients with chronic liver disease or acute-on-chronic liver failure (ACLF). Only a few studies have investigated the management of ICH in ACLF. Here, we present an uncommon case of acute-onset severe hyperammonemia in a patient with cirrhosis who developed fulminant ICH. Rapid institution of renal placement therapy and therapeutic plasma exchange achieved a dramatic reduction in the serum ammonia level, but did not slow the patient’s rapid neurological deterioration.